Light and sound - emerging imaging techniques for inflammatory bowel disease - Knieling, Ferdinand; Waldner, Maximilian (World Journal of Gastroenterology, 2016)
Patients with inflammatory bowel disease are known to have a high demand of recurrent evaluation for therapy and disease activity. Further, the risk of developing cancer during the disease progression is increasing from year to year. New, mostly non-radiant, quick to perform and quantitative methods are challenging, conventional endoscopy with biopsy as gold standard. Especially, new physical imaging approaches utilizing light and sound waves have facilitated the development of advanced functional and molecular modalities. Besides these advantages they hold the promise to predict personalized therapeutic responses and to spare frequent invasive procedures. Within this article we highlight their potential for initial diagnosis, assessment of disease activity and surveillance of cancer development in established techniques and recent advances such as wide-view full-spectrum endoscopy, chromoendoscopy, autofluorescence endoscopy, endocytoscopy, confocal laser endoscopy, multiphoton endoscopy, molecular imaging endoscopy, B-mode and Doppler ultrasound, contrast-enhanced ultrasound, ultrasound molecular imaging, and elastography.
EVALuna2:2167